Variable clinical expression in patients with a germline MEN1 disease gene mutation: clues to a genotype-phenotype correlation (Clinics, 2012)
Multiple endocrine neoplasia type 1 is an inherited endocrine tumor syndrome, predominantly characterized by tumors of the parathyroid glands, gastroenteropancreatic tumors, pituitary adenomas, adrenal adenomas, and neuroendocrine tumors of the thymus, lungs or stomach. Multiple endocrine neoplasia type 1 is caused by germline mutations of the multiple endocrine neoplasia type 1 tumor suppressor gene. The initial germline mutation, loss of the wild-type allele, and modifying genetic and possibly epigenetic and environmental events eventually result in multiple endocrine neoplasia type 1 tumors. Our understanding of the function of the multiple endocrine neoplasia type 1 gene product, menin, has increased significantly over the years. However, to date, no clear genotype-phenotype correlation has been established. In this review we discuss reports on exceptional clinical presentations of multiple endocrine neoplasia type 1, which may provide more insight into the pathogenesis of this disorder and offer clues for a possible genotype-phenotype correlation.